A small and robust active beamstop for scattering experiments on high‐brilliance undulator beamlines. (3rd February 2015) - Blanchet, Clement E.; Hermes, Christoph; Svergun, Dmitri I.; Fiedler, Stefan
<x xml:space="preserve">Abstract</x> A small active in‐vacuum beamstop has been developed to monitor the flux of intense third‐generation synchrotron X‐ray beams protecting the downstream detector from the direct beam. Standard active beamstops, where a built‐in diode directly absorbs the beam, have limitations in size and lifetime. In the present design, a silicon PIN diode detects the photons back‐scattered from a cavity in the beamstop. This approach drastically reduces the radiation dose on the diode and thus increases its lifetime. The beamstop with a diameter of 2 mm has been fabricated to meet the requirements for the P12 bioSAXS beamline of EMBL Hamburg at PETRA III (DESY). The beamstop is in regular user operation at the beamline and displays a good response over the range of energies tested (6–20 keV). Further miniaturization of the diode is easily possible as its size is not limited by the PIN diode used.